Trends in cost and consumption of essential medicines for non-communicable diseases in Azerbaijan, Georgia, and Uzbekistan, from 2019 to 2021. - Ninell Kadyrova; Dzintars Gotham; Stanislav Kniazkov; Elsever Aghayev; Polad Hajibalayev; Zohid Ermatov; Natasha Azzopardi Muscat (PLoS ONE)
Background Access to medicines is a global priority. Azerbaijan, Georgia, and Uzbekistan have different approaches to pricing policies for pharmaceuticals. The aim of this study was to analyze recent trends in the consumption and prices of non-communicable disease (NCD) medicines in Azerbaijan, Georgia, and Uzbekistan, in the outpatient setting. Methods We included medicines for asthma and COPD, cancer, cardiovascular disease, diabetes, epilepsy, and mental disorders. Sales data for pharmaceutical products in community pharmacies were extracted from a commercial database. Changes in consumption and prices were analyzed across all included NCD medicines, by disease category and pharmacological group. Results Consumption of NCD medicines was highest in Georgia, at twice the levels in Azerbaijan, and four times levels in Uzbekistan. Average prices of NCD medicines, weighted by consumption, increased by 26% in Georgia, but decreased by 3% in Azerbaijan and by 0.1% in Uzbekistan. Prices increased for all disease groups in Georgia (from +13% for epilepsy medicines to +86% for cancer), varied by group in Uzbekistan (from -22% for epilepsy medicines to +47% for cancer), while changes in Azerbaijan were smaller in magnitude (from -4% for medicines for cardiovascular disease to +11% for cancer). Cancer medicines had markedly higher prices in Uzbekistan, and asthma and COPD medicines had markedly higher prices in Azerbaijan and Uzbekistan. Conclusions Georgia showed the highest outpatient consumption of NCD medicines, suggesting the broadest access to treatment. However, Georgia also saw marked price increases, greater than in the other countries. In Georgia, where there was no price regulation, widespread price increases and increases in consumption both contribute to increasing pharmaceutical expenditures. In Azerbaijan and Uzbekistan, increases in outpatient pharmaceutical expenditures were primarily driven by increases in consumption, rather than increases in price. Comparing trends in consumption and pricing can identify gaps in access and inform future policy approaches.